Gestational fine particulate matter exposure and perinatal outcomes in the ECHO cohort: Associations across pregnancy windows - Adaeze W. Nzegwu; Aisha S. Dickerson; Kristin Miller; Adam Szpiro; Alison E. Hipwell; Amy J. Elliot; Amy M. Padula; Anne L. Dunlop; Anne P. Starling; Assiamira Ferrara; Carrie V. Breton; Christine T. Loftus; et al. (Environmental Research, 2026)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Seaweed ethnobotany of eastern Sorsogon, Philippines - Richard V. Dumilag; Teresa Haide R. Belgica; Lynn C. Mendoza; Janet M. Hibay; Abel E. Arevalo; Mark Ariel D. Malto; Elden G. Orgela; Mabille R. Longavela; Laurence Elmer H. Corral; Ruby D. Olipany; Caesar Franz C. Ruiz; Cynthia B. Mintu; et al. (Algae, 2022)
Knowledge on the seaweeds of eastern Sorsogon in the Philippines is uneven. Not only is eastern Sorsogon among the areas of high seaweed diversity but locals there have interacted with seaweeds for ages. Despite seaweeds’ assumed importance to Sorsoganon, ethnobotanical records are missing. In this study, we documented the traditional knowledge on seaweed use and determined the rate of knowledge transmission among the locals of eastern Sorsogon. Vernacular names and modes of preparation were given of the 12 identified species bearing culinary and medicinal importance. Ten species were eaten while three were used therapeutically. Based on ethnobotanical indices, Caulerpa chemnitzia ecad turbinata and Gelidiella acerosa were the most important seaweeds. The least cited was Caulerpa racemosa. Our study demonstrated that most of the seaweed resources in eastern Sorsogon remain largely untapped, as the identified ethnotaxa were only about 5% of the total seaweed species diversity reported for the area. The seaweed knowledge in eastern Sorsogon appeared to be homogenous across age groups with primary sources of knowledge biased towards female relatives (mothers and grandmothers) and to children as inheritors. Cessation of seaweed knowledge may come at a potential cost, as a significant fraction of the population did not transmit their knowledge to others. Our study furthered the interest in providing sophisticated resource management recommendations that consider the relationships of traditional and scientific knowledge of seaweed selection and use in eastern Sorsogon and beyond.

Inter-laboratory automation of the in vitro micronucleus assay using imaging flow cytometry and deep learning - John W. Wills; Jatin R. Verma; Benjamin J. Rees; Danielle S. G. Harte; Qiellor Haxhiraj; Claire M. Barnes; Rachel Barnes; Matthew A. Rodrigues; Minh Doan; Andrew Filby; Rachel E. Hewitt; Catherine A. Thornton; et al. (Archives of Toxicology, 2021)
The in vitro micronucleus assay is a globally significant method for DNA damage quantification used for regulatory compound safety testing in addition to inter-individual monitoring of environmental, lifestyle and occupational factors. However, it relies on time-consuming and user-subjective manual scoring. Here we show that imaging flow cytometry and deep learning image classification represents a capable platform for automated, inter-laboratory operation. Images were captured for the cytokinesis-block micronucleus (CBMN) assay across three laboratories using methyl methanesulphonate (1.25–5.0 μg/mL) and/or carbendazim (0.8–1.6 μg/mL) exposures to TK6 cells. Human-scored image sets were assembled and used to train and test the classification abilities of the “DeepFlow” neural network in both intra- and inter-laboratory contexts. Harnessing image diversity across laboratories yielded a network able to score unseen data from an entirely new laboratory without any user configuration. Image classification accuracies of 98%, 95%, 82% and 85% were achieved for ‘mononucleates’, ‘binucleates’, ‘mononucleates with MN’ and ‘binucleates with MN’, respectively. Successful classifications of ‘trinucleates’ (90%) and ‘tetranucleates’ (88%) in addition to ‘other or unscorable’ phenotypes (96%) were also achieved. Attempts to classify extremely rare, tri- and tetranucleated cells with micronuclei into their own categories were less successful (≤ 57%). Benchmark dose analyses of human or automatically scored micronucleus frequency data yielded quantitation of the same equipotent concentration regardless of scoring method. We conclude that this automated approach offers significant potential to broaden the practical utility of the CBMN method across industry, research and clinical domains. We share our strategy using openly-accessible frameworks.

Heavy metal concentrations in soils and vegetation in urban areas of Quezon City, Philippines - Ian A. Navarrete; Christella C. Gabiana; Joan Ruby E. Dumo; Severino G. Salmo; Maria Aileen Leah G. Guzman; Nestor S. Valera; Emilyn Q. Espiritu (Environmental Monitoring and Assessment, 2017)

BioEarth: Envisioning and developing a new regional earth system model to inform natural and agricultural resource management - Jennifer C. Adam; Jennie C. Stephens; Serena H. Chung; Michael P. Brady; R. David Evans; Chad E. Kruger; Brian K. Lamb; Mingliang Liu; Claudio O. Stöckle; Joseph K. Vaughan; Kirti Rajagopalan; John A. Harrison; et al. (Climatic Change, 2015)

Non‐native acylated homoserine lactones reveal that LuxIR quorum sensing promotes symbiont stability - Sarah V. Studer; Julia A. Schwartzman; Jessica S. Ho; Grant D. Geske; Helen E. Blackwell; Edward G. Ruby (Environmental Microbiology, 2014)
Summary Quorum sensing, a group behaviour coordinated by a diffusible pheromone signal and a cognate receptor, is typical of bacteria that form symbioses with plants and animals. LuxIR ‐type N ‐acyl L‐homoserine ( AHL ) quorum sensing is common in Gram‐negative Proteobacteria , and many members of this group have additional quorum‐sensing networks. The bioluminescent symbiont V ibrio fischeri encodes two AHL signal synthases: AinS and LuxI . AinS ‐dependent quorum sensing converges with LuxI ‐dependent quorum sensing at the LuxR regulatory element. Both AinS ‐ and LuxI ‐mediated signalling are required for efficient and persistent colonization of the squid host, E uprymna scolopes . The basis of the mutualism is symbiont bioluminescence, which is regulated by both LuxI ‐ and AinS ‐dependent quorum sensing, and is essential for maintaining a colonization of the host. Here, we used chemical and genetic approaches to probe the dynamics of LuxI ‐ and AinS ‐mediated regulation of bioluminescence during symbiosis. We demonstrate that both native AHLs and non‐native AHL analogues can be used to non‐invasively and specifically modulate induction of symbiotic bioluminescence via LuxI ‐dependent quorum sensing. Our data suggest that the first day of colonization, during which symbiont bioluminescence is induced by LuxIR , is a critical period that determines the stability of the V . fischeri population once symbiosis is established.

Polyphyly of non‐bioluminescent Vibrio fischeri sharing a lux ‐locus deletion - M. S. Wollenberg; S. P. Preheim; M. F. Polz; E. G. Ruby (Environmental Microbiology, 2012)
Summary This study reports the first description and molecular characterization of naturally occurring, non‐bioluminescent strains of Vibrio fischeri . These ‘dark’ V. fischeri strains remained non‐bioluminescent even after treatment with both autoinducer and aldehyde, substrate additions that typically maximize light production in dim strains of luminous bacteria. Surprisingly, the entire lux locus (eight genes) was absent in over 97% of these dark V. fischeri strains. Although these strains were all collected from a Massachusetts (USA) estuary in 2007, phylogenetic reconstructions allowed us to reject the hypothesis that these newly described non‐bioluminescent strains exhibit monophyly within the V. fischeri clade. These dark strains exhibited a competitive disadvantage against native bioluminescent strains when colonizing the light organ of the model V. fischeri host, the Hawaiian bobtail squid Euprymna scolopes . Significantly, we believe that the data collected in this study may suggest the first observation of a functional, parallel locus‐deletion event among independent lineages of a non‐pathogenic bacterial species.

Symbiosis research, technology, and education: Proceedings of the 6th International Symbiosis Society Congress held in Madison Wisconsin, USA, August 2009 - Heidi Goodrich-Blair; Jean-Michel Ané; James D. Bever; Seth R. Bordenstein; Monika Bright; John M. Chaston; Keith Clay; Cameron R. Currie; Angela E. Douglas; Nicole Gerardo; Maria J. Harrison; Ruth E. Ley; et al. (Symbiosis, 2010)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

TheVibrio fischeri sapABCDF locus is required for normal growth, both in culture and in symbiosis - Claudia Lupp; Robert E. W. Hancock; Edward G. Ruby (Archives of Microbiology, 2002)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)

Cryptic luminescence in the cold-water fish pathogen Vibrio salmonicida - P. M. Fidopiastis; Henning Sørum; E. G. Ruby (Archives of Microbiology, 1999)

Growth and flagellation of Vibrio fischeri during initiation of the sepiolid squid light organ symbiosis - E. G. Ruby; L. M. Asato (Archives of Microbiology, 1993)

Unbalanced growth as a normal feature of development of Bdellovibrio bacteriovorus - K. M. Gray; E. G. Ruby (Archives of Microbiology, 1989)